Slovenska ljudska balada v srednješolskem izobraževanju - pastorka književnosti? - Golež Kaučič, Marjetka (Jezik in slovstvo, 2019)
The article attempts to determine how and by what means the Slovenian folk ballad is presented in the upper-secondary education process, based on a review and analysis of selected Slovenian curricula, including handbooks, textbooks and e-textbooks. For this purpose, we focus on the characteristics and features of the Slovenian ballad, as well as on the examples and their analysis offered in these publications. We also examine the experiences of some upper-secondary school teachers in regard to the topic. At the same time, the article focuses on the European and American educational space, introducing the inclusion of knowledge of folklore at the undergraduate level for those who teach folklore and the ballad, as well as cases of how this knowledge is presented in international curricula. It is concluded that the curricula and publications that bring knowledge about the Slovenian folk ballad need revision, and that a multidisciplinary view of the Slovenian folk ballad is required. The author believes that this art genre is of exceptional cultural significance and offers suggestions for improving education about folk ballads and the participation of folklorists.
Keywords: balade; identifikacija; klasifikacija; poučevanje; slovenska književnost; slovenska ljudska balada; srednješolski izobraževalni proces; učni načrti